Програмний контроль часу використання інструментальних засобів - Гаєвий, А. О. (ХНУРЕ, 2025)
The work focuses on the development of a desktop application to enhance self-control and reduce dependence on instant gratification sources, such as YouTube Shorts and games. Using WPF and C#, the application allows users to set time limits on unproductive programs, track progress in achieving goals, and foster habits for independent productivity. Experimental use demonstrates its ef-fectiveness in minimizing distractions and improving focus.
Keywords: контроль часу; self-control